Philosophy-screens from cinema to the digital revolution - Carbone, Mauro, 1956- (SUNY series in contemporary continental philosophy., 2019)
"In The Flesh of Images, Mauro Carbone analyzed Merleau-Ponty's interest in film as it relates to his aesthetic theory. Philosophy-Screens broadens the work undertaken in this earlier book, looking at the ideas of other twentieth-century thinkers concerning the relationship between philosophy and film, and also extending that analysis to address the wider proliferation of screens in the twenty-first century. In the first part of the book, Carbone examines the ways that Sartre, Merleau-Ponty, Lyotard, and Deleuze grappled with the philosophical significance of cinema as a novel aesthetic medium unfolding in the twentieth century. He then considers the significance of this philosophical framework for understanding the digital revolution, in particular the extent to we are increasingly and comprehensively connected with screens. Smart phones, tablets, and computers have become a primary referential optical apparatus for everyday life in ways that influence the experience not only of seeing but also of thinking and desiring. Carbone's Philosophy-Screens follows Deleuze's call for "a philosophy-cinema" that can account for these fundamental changes in perception and aesthetic production, and adapts it to twenty-first century concerns"--